Choujin X. Volume 12 - Ishida, Sui (VIZ Media, LLC, 2026)
Best friends Tokio and Azuma do everything together, even if most of the time it feels like Tokio is just stumbling along in Azuma's cooler, more talented footsteps. But when they're attacked one night by a superhuman mutant called a choujin, Tokio finally has a chance to shine-by turning into a choujin himself! Azuma refused to admit defeat when he and his Yamato Mori comrades were faced with impossible odds, and while his wild bravery might have bought the team more time, it's also catapulted him into an inescapable chaos state. Locked inside his teeming mind, Azuma comes face-to-face with some terrible truths about himself. Can he break out of the chaos coma in time to help his friends, or will the shocking revelation of his sordid history trap him in his thoughts forever?!